Study on Electrochemical Copolymerization of Aniline and 3-Methylthiophene in HMIMBF4 Ionic Liquid and Its Properties - 张爱健 张贵荣 杨广达 敖凤国 陆嘉星 (Chinese journal of chemistry, 2007)
Electrochemical polymerization of aniline and 3-methylthiophene has been accomplished in 1-methylimidazium tetrafluoroborate （HMIMBF4） ionic liquid. Homopolymer and copolymers of aniline and 3-methylthiophene were obtained successfully. The copolymer was studied by cyclic voltammetry and electrochemical impedance spectroscopy. The formation of copolymer has been confirmed by FT-IR and UV spectra. The atomic force microscope （AFM） was used for microstructural analysis. Both the homopolymer and the copolymer had the catalytic activity for the hydroquinone.